2023
DOI: 10.2147/opth.s431356
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of Phacoemulsification and Endocyclophotocoagulation with Either Dual Blade Goniotomy (PEcK) or Two Trabecular Stents (ICE2)

Hani El Helwe,
Blake Oberfeld,
Fatemeh Golsoorat Pahlaviani
et al.

Abstract: Purpose To compare outcomes of phacoemulsification and endocyclophotocoagulation with either dual blade goniotomy (PEcK) or two trabecular stents (ICE2). Setting Retrospective, nonrandomized comparative study from a level 3 triage center. Methods One hundred and seventy charts and a total of 1294 visits were reviewed following either PEcK or ICE2 from 2018 to 2022. One hundred and twenty-eight patients had PEcK and 42 underwent ICE2. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…At 12 months, the studies reported greater mean IOP reduction following PEcK compared to ICE (5.0 to 5.1 mmHg and 2.3 to 3.1 mmHg, respectively), as well as similar or greater mean medication reduction (1.4 to 1.6 fewer medications and 1.0 fewer medications, respectively). 12 , 34 …”
Section: Introductionmentioning
confidence: 99%
“…At 12 months, the studies reported greater mean IOP reduction following PEcK compared to ICE (5.0 to 5.1 mmHg and 2.3 to 3.1 mmHg, respectively), as well as similar or greater mean medication reduction (1.4 to 1.6 fewer medications and 1.0 fewer medications, respectively). 12 , 34 …”
Section: Introductionmentioning
confidence: 99%